If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13y + -24 = 119 Reorder the terms: -24 + 13y = 119 Solving -24 + 13y = 119 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 13y = 119 + 24 Combine like terms: -24 + 24 = 0 0 + 13y = 119 + 24 13y = 119 + 24 Combine like terms: 119 + 24 = 143 13y = 143 Divide each side by '13'. y = 11 Simplifying y = 11
| (3x^2+6x-9)(x-1)=0 | | 55=4+3(x+2) | | 6x+25=7 | | 3x-1=-40 | | 6(e+4)=-18 | | x(x+7)=12 | | 16x^2+24x=7 | | P+3=4 | | x^4-4x^3-12x^2+28x+12=0 | | -2=x/4-3 | | 3(4x+16)=9x+12 | | 19=n*8 | | 3-4m=10m+10 | | (2x+4)(2x-4)=-4x-16 | | T+7=9 | | -2(n+1)=-1(2n+5) | | -4=x/7+3 | | 17+-d=9 | | 15=-2x+3 | | 3m+14=5m-4 | | P+75=120 | | 6m+11=8m-5 | | (4x^2+22x-42)(x+7)=0 | | 13x-173=4x-11 | | 6m+9=8m-5 | | 19-.25(X+8)-x=2 | | b/9+4=7 | | -12d-6=-2(d+3)-10d | | 32=16+.4(20-10X) | | 15x+29(x-2)=206 | | 10-10x=64-31x | | -(a+9)=4(3-a) |